Attitudes of nurses working in psychiatry clinics towards alcohol and substance addiction - Karadağ, Feyzanur; Babaoğlu, Elçin (Journal of Dependence, 2022)
Objective: This study was conducted to examine the beliefs of nurses working in psychiatry clinics about substance addiction. Method: The sample of the descriptive study consisted of 103 nurses working in psychiatry clinics in Turkey. As a data collection tool; “Nurses Descriptive Feature Form” and “Beliefs Related to Addictions Scale” were used. Results: The mean total score of the sub-dimensions of the Addiction Belief Scale was 3.02 (N=103), the standard deviation was 0.79. Since the highest score for each sub-dimension in the scale was 5, the nurses got the highest mean score (3.55±1.15) from ABS sub-dimensions from the “Reliance on experts”. It was determined that they got the lowest average score (2.46±1.00) from the “Responsibility for Actions” sub-dimension. Conclusion: A significant difference was found in favor of the nurses who are dependent individuals in their families or close relatives in the “Responsibility for Recovery” sub-dimension of the scale, according to the variable of being dependent individuals in the family or relatives of the nurses. In the “Chronic Disease” sub-dimension, a significant difference was found in favor of the nurses who were satisfied with the unit they worked in.